The Economic Impacts of Digital Agriculture Apps in Developing Countries: Focus on India, Bangladesh, Nepal, and Sri Lanka. - Mr. Sunil Madan, Dr. Rohit Jadhav, Dr. Aswinkumar Chawan, Dr. Baban More, Dr. Ashok Chikte (Journal of Daoist Studies, 2026)
Digital agriculture applications are transforming agricultural practices across South Asia, providing smallholder farmers with unprecedented access to agronomic, extension, advisory, market, weather, financial, and input services through a range of mobile apps offered by public and private organizations. This research paper examines the economic impacts of digital agriculture apps in India, Bangladesh, Nepal, and Sri Lanka, synthesizing evidence from experimental studies, meta-analyses, and platform evaluations. Findings reveal significant positive impacts: digital interventions increase crop yields by 2-21%, boost farmer incomes by 6-29%, and enhance input adoption rates by 2-23%. However, adoption remains constrained by infrastructure gaps, digital literacy barriers, and socioeconomic factors. India has the most advanced agritech ecosystem, with platforms like DeHaat and AgroStar serving millions of farmers, while Bangladesh, Nepal, and Sri Lanka show emerging but promising digital agriculture landscapes. The study recommends targeted policy interventions, including expanding digital infrastructure, developing localized content, and adopting hybrid digital-physical extension models to maximize economic benefits for smallholder farmers.